FAKTOR YANG BERHUBUNGAN DENGAN GANGGUAN FUNGSI PARU PEKERJA INDUSTRI MEBEL - Novrizal Ramadan; Saddam Husen, Rizka Adinda Saragih, Reza Pahlevi, Azizah Budiana, Mhd Ibnu Sina, Tri Niswati Utami (Jurnal Kesehatan, 2023)
Exposure to dust can cause various occupational diseases resulting in impaired lung function and disability. Various factors that influence the emergence of diseases or disorders of the respiratory tract due to dust are dust factors, which include particle size, shape, concentration, solubility and chemical properties, as well as length of exposure. Every job has potential hazards in the form of occupational diseases. Based on data from the International Labor Organization (ILO) in 2013, 160 workers worldwide experience work-related illness. Impaired lung function is still one of the occupational diseases with an incidence of around one case per 1000 workers each year. Stone mining is a job in the informal sector that has a high risk of occupational lung disease due to inhalation of dust in the work environment. This study aims to determine the factors associated with impaired lung function in workers. The research design uses a literature review in conducting a literature search, the researcher utilizes the Google Scholar database facility with a search strategy using Indonesian keywords. The literature used as a source in this research is only articles/journals published between 2017 and 2022 (5 years), with the criteria of having relevance to the research topic.